Nicotinamide mononucleotide attenuates HIF-1α activation and fibrosis in hypoxic adipose tissue via NAD+/SIRT1 axis - Wu, Keke; Li, Biao; Ma, Yingxu; Tu, Tao; Lin, Qiuzhen; Zhu, Jiayi; Zhou, Yong; Liu, Na; Liu, Qiming (Frontiers in Endocrinology, 2023)
Background: Fibrosis is increasingly considered as a major contributor to adipose tissue dysfunction. Hypoxic activation of hypoxia-inducible factor 1α (HIF-1α) induces a profibrotic transcription, leading to adipose fibrosis. Nicotinamide mononucleotide (NMN), a member of the vitamin B3 family, has been shown to relieve hepatic and cardiac fibrosis, but its effects on hypoxic adipose fibrosis and the underlying mechanism remain unclear. We aimed to elucidate the roles of NMN in regulating HIF-1α and fibrosis in hypoxic adipose tissue Methods: Mice were placed in a hypobaric chamber for four weeks to induce adipose fibrosis. NMN (500 mg/kg, every three days, i.p) was administered by intraperitoneal injection. In vitro, Stromal vascular fractions (SVFs) cells were treated with hypoxia with or without NMN (200μM), sirtinol (25μM, a SIRT1 inhibitor), and CoCl2 (100μM, a HIF1α enhancer). The effects of NMN on hypoxia-associated adipose fibrosis, inflammation, NAD+/SIRT1 axis alteration, and HIF-1α activation were evaluated by real-time polymerase chain reaction, western blots, immunohistochemistry staining, immunoprecipitation, and assay kits. Results: Mice placed in a hypoxic chamber for four weeks showed obvious adipose fibrosis and inflammation, which were attenuated by NMN. NMN also restore the compromised NAD+/SIRT1 axis and inhibited the activation of HIF-1α induced by hypoxia. In hypoxia-induced SVFs, the SIRT1 inhibitor sirtinol blocked the anti-fibrotic and anti-inflammatory effects of NMN and upregulated the HIF-1α and its acetylation level. The HIF1α stabilizer CoCl2 showed similar effects as sirtinol. Conclusion: NMN effectively attenuated HIF-1α activation-induced adipose fibrosis and inflammation by restoring the compromised NAD+/SIRT1 axis.